Analisis Framing dan Causal Cognitive Mapping dalam Pengambilan Keputusan Strategik: Suatu Studi Eksperimental - Yusnaini Yusnaini (The Indonesian Journal of Accounting Research, 2013)
The objectives of this research are to examine and to give empirical evidence about framing and causal cognitive mapping effect on strategic decision making under uncertainty condition.  The first hypothesis proposed is that there is bias in decision making caused by presented information of positive and negative framing. The second hypothesis suggests that the bias can be eliminated through causal cognitive mapping technique. In this research the bias that occurred can be measured by the risk of decision making preference, namely risk averse or risk seeking tendency.This research uses 2 x 2 between subject experimental designs.  Participants are 114 student of MM UGM Jakarta executive class. In order to examine the hypotheses, independent sample t-test is used.  The result is that the difference of average risk preference between participants who receive positive framing and participants who receive negative framing shows bias in decision making. The result of the test shows the supports the proposed hypotheses. This research empirically shows that framing and causal cognitive mapping technique affect strategic decision making under uncertainty. Specifically it can be concluded that: (1) decision makers that receive information in positive and negative framing will undergo bias in decision making; (2) participant who receive positive framing will tend to risk averse, whereas participant who receive negative framing will tend to risk seeking; (3) causal cognitive mapping technique can decrease bias as impact of framing in strategic decision making under uncertainty.